Aza‐oxyallyl Cations and Their Applications in (3+m) Cycloaddition Reactions. Issue 47 (9th November 2022) - Deeksha; Singh, Ritesh
Abstract: Aza‐oxyallyl cations, as proposed by Sheehan in the 1960s have garnered significant attention among the synthetic organic community, owing to their diverse reactivity profile for constructing N‐scaffolds of biological interest. During its initial growth, aza‐oxyallyl cations were used effectively as a 3‐unit synthon as 1, 3 dipoles to create N‐heterocycles via cycloaddition reactions, wherein aza‐oxyallyl cation served as electrophilic counterpart. Recently, new variations of aza‐oxyallyl cations reactivity have been reported, including its usage as a 1, 4 dipole in cycloaddition reactions, domino reactions, and the unique alkylating ability of heteroatoms. This review article provides an update of the recent developments in this area and the prevailing mechanistic insight. Abstract : Aza‐oxyallyl cations have garnered significant attention among the synthetic organic community as a versatile synthon for the construction of N‐heterocycles. This review article provides an update of the recent developments in this area and the prevailing mechanistic insight.